Neuroticism and Interpretive Bias as Risk Factors for Anxiety and Depression. (July 2020) - Vinograd, Meghan; Williams, Alexander; Sun, Michael; Bobova, Lyuba; Wolitzky-Taylor, Kate B.; Vrshek-Schallhorn, Suzanne; Mineka, Susan; Zinbarg, Richard E.; Craske, Michelle G.
Neuroticism has been associated with depression and anxiety both cross-sectionally and longitudinally. Interpretive bias has been associated with depression and anxiety, primarily in cross-sectional and bias induction studies. The purpose of the current study was to examine the role of interpretive bias as a prospective risk factor and a mediator of the relation between neuroticism and depressive and anxious symptoms in young adults assessed longitudinally. Neuroticism significantly predicted a broad general-distress dimension but not intermediate fears and anhedonia-apprehension dimensions or a narrow social-fears dimension. Neuroticism also significantly predicted negative interpretive bias for social scenarios. Negative interpretive bias for social scenarios did not significantly predict dimension scores, nor did it mediate the relation between neuroticism and general distress or social fears. These results suggest that although neuroticism relates to negative interpretive bias, its risk for symptoms of depression and anxiety is at most weakly conferred through negative interpretive bias.